The Role of Automated Decision-Making in Modern Administrative Law: Challenges and Data Protection Implications - Grega Rudolf; Polonca Kovač (Central European Public Administration Review)
Purpose: The integration of artificial intelligence (AI) in automated decision-making (ADM) represents a transformative moment in public administration. This paper explores the incorporation of ADM systems into administrative procedures, focusing on their impact on personal data protection and the fundamental principles underpinning administrative law. Design/Methodology/Approach: Utilising a combination of descriptive, normative, and doctrinal research methods, the study draws on recent regulatory initiatives, analyses selected ADM use cases in Slovenia and abroad, and closely examines the 2023 Schufa case decided by the Court of Justice of the European Union (CJEU). By combining theoretical perspectives with practical insights, the research provides a comparative analysis within the context of EU and Slovenian legal frameworks. Findings: The study assesses how ADM systems interact with, and potentially reshape, key principles of administrative and data protection law. It presents a clear picture of the legislative, organisational, and technological changes required to ensure that ADM systems align with existing legal frameworks. Academic Contribution to the Field: By offering valuable guidance for public administration professionals, the paper enhances the understanding of implementing ADM technologies in administrative practice. Its insights assist policymakers and legislators in crafting regulations that embrace the benefits of AI while ensuring these systems are subject to proper oversight. Research/Practical/Social Implications: The deployment of ADM systems must align with legal principles to maintain transparency, accountability, and the protection of fundamental rights. This paper highlights the importance of not only understanding the legal implications but also ensuring that ADM technologies uphold standards of good governance. Originality/Value: This research extends the boundaries of established legal frameworks and raises critical questions about how core principles of administrative and data protection law can adapt to new technologies. The challenge lies in leveraging AI to increase efficiency while ensuring these innovations respect individual rights, safeguard the public interest, and uphold standards of good administration and governance.